2011
DOI: 10.1016/j.actbio.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric endoaortic paving: Mechanical, thermoforming, and degradation properties of polycaprolactone/polyurethane blends for cardiovascular applications

Abstract: Polymeric endoaortic paving (PEAP) is a process by which a polymer is endovascularly delivered and thermoformed to coat or “pave” the lumen of the aorta. This method may offer an improvement to conventional endoaortic therapy in allowing conformal graft application with reduced risk of endoleak and customization to complex patient geometries. Polycaprolactone (PCL)/polyurethane (PU) blends of various blend ratios were assessed as a potential material for PEAP by characterizing their mechanical, thermoforming, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 40 publications
3
53
0
Order By: Relevance
“…Due to their outstanding properties, PUs are widely used in automotive (instrument panel, belt, seals), electric/electronic (cable jacketing, mobile phones), transportation (conveyor belt, tyres), footwear (shoe and shoe sole), medical (catheters) fields, sporting goods, leisure articles (grips) etc. [3][4][5][6][7][8]. Linear PUs are traditionally produced by reacting diisocyanates (hard segments), long-chain diols of polyesters and/or polyethers (soft segments) and with short-chain diols (socalled chain extenders).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their outstanding properties, PUs are widely used in automotive (instrument panel, belt, seals), electric/electronic (cable jacketing, mobile phones), transportation (conveyor belt, tyres), footwear (shoe and shoe sole), medical (catheters) fields, sporting goods, leisure articles (grips) etc. [3][4][5][6][7][8]. Linear PUs are traditionally produced by reacting diisocyanates (hard segments), long-chain diols of polyesters and/or polyethers (soft segments) and with short-chain diols (socalled chain extenders).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this polymer can be used in various medical practices. [14,15] Polycaprolactone is a deformable polymer and its biodegradation occurs slowly over a long period of time. It is also widely biocompatible, [16] which is the main reason we chose it for our current study.…”
Section: Discussionmentioning
confidence: 99%
“…3 Blends of PCL (MW 70,000, Fisher Scientific, NC9498824) and PU (Lubrizol, Tecoflex Ò SG-80A) were made by dissolving them in chloroform, yielding 10/90 and 50/50 ratios (wt% PCL/PU). Sheets were fabricated via solvent casting.…”
Section: Pcl/pu Specimensmentioning
confidence: 99%
“…1,19,21,29 Testing in our laboratory revealed that PCL/PU blends are thermoformable at 55°C, resistant to biodegradation, and have mechanical properties that can be controlled by varying PCL/ PU ratios. 3 In order for PEAP to prevent AAA rupture and provide a viable option to treat AAA, it must reduce aneurysm wall stress at least as effectively as stentgrafts. Various computational techniques have been used to estimate stresses in AAA, some of which include finite element modeling (FEM), 10,13 coupled fluid-structure interaction simulations (FSI), 22,26 and more recently porohyperelastic modeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation